Reduced Switch Multilevel Inverter Topologies And Modulation Techniques For Renewable Energy Applications - et.al, Ujwala Gajula (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multilevel inverters (MLIs) have been extensively used and gained interest over last few decades in industrial and grid connected renewable energy applications because of its numerous merits. Besides various advantages like obtaining reduced harmonic distortion and lesser dv/dt stress across switches it has the capability of generating any number of levels. The theory of multilevel concept was initiated for high power and high/medium voltage applications as they are helpful in interfacing with renewable energy sources. By proper combination of the switches it generates a stair case output with reduced harmonic distortion because of this MLI is widely used and it became one of the advanced power converter topology. The rise of new topologies has attained importance over conventional multilevel inverter topologies, which generates more number of levels with reduced switch components. This paper presents various conventional MLI topologies and hybrid MLI topologies for renewable energy applications. Also, this review paper includes different modulation strategies which plays an important role to improve the overall performance of MLI.